The Diffusion of Knowledge during the British Industrial Revolution. Issue 2 (22nd March 2023) - Galofré-Vilà, Gregori
Abstract: While technological progress played a central role in the British Industrial Revolution, statistical evidence on how inventors and entrepreneurs engaged in the process of technological innovation has typically received minor attention. In this paper I use quantitative methods to show that counties with a relatively high number of informal networks −in the form of Freemasonry, friendly societies, libraries, and booksellers− experienced more innovation as measured by new patents and exhibits at the 1851 Crystal Palace World's Fair. Qualitative evidence and propensity score matching suggest that the mechanisms highlighted here were an important part of British technological leadership. Economic factors cannot account for these patterns.